Effects of credit market freedom on output reallocation in China’s banking sector through the intermediation of cost X-inefficiency - Yap, Woon Kan; Law, Siong Hock; Abdul Ghani, Judhiana (Central University of Finance and Economics, 2019)
This study examines the effects of credit market freedom on the dynamics of Chinese banks’ output reallocation through the intermediation of cost X-inefficiency. We find two distinct regimes that underpin the mechanism of foreign banks and domestic banks respectively. Credit market freedom is found to significantly foster cost X-efficiency among the foreign banks, which subsequently lead to marginally more efficient allocation of outputs with efficient foreign banks gain market shares at the expense of those inefficient ones. On the other hand, the same circuit of effects does not apply to the domestic banks. Therefore, arguably foreign banks attach more importance to efficiency, while domestic banks leech on to state protection for their respective existence.